PENERAPAN METODE PERBANDINGAN EXPONENSIAL (MPE) PENENTUAN PENERIMAAN BERAS SEJAHTRA (RASTRA) DI DESA TOBU - Petrus Katemba; Niklinton Nehemia Neolak (Elkom : Jurnal Elektronika dan Komputer, 2021)
This research was made with the aim of developing the application of determining the recipient of Rastra (Rice Prosperous) aid in Tobu Village. South middle Timor district by applying the exponential comparison method. Variables or criteria used in this study are work, income, number of dependents, building area and housing conditions and detailed criteria on each variable. This research succeeded in developing an application ranking community beneficiaries of Rastra in Tobu village by using the exponential comparison method (MPE). In this application provides a graphical display feature, print reports that will be used to print and view the results of the ranking of people who are entitled to receive Sejahtera ria.